Congregational involvement in HIV: A qualitative comparative analysis of factors influencing HIV activity among diverse urban congregations. (February 2020) - Mendel, Peter; Green, Harold D.; Palar, Kartika; Kanouse, David E.; Bluthenthal, Ricky N.; Mata, Michael A.; Oden, Clyde W.; Derose, Kathryn P.
Abstract: Religious congregations can potentially reach disproportionately affected populations with HIV programming, however, factors that influence congregational involvement in HIV are not well-studied. Utilizing comparative case methods and in-depth qualitative data from a diverse sample of 14 urban congregations, we examine a range of attitudinal, organizational, resource, and demographic factors to systematically identify different case scenarios—i.e., combinations of characteristics—associated with the level and types of HIV activities in which the congregational cases tended to be involved. For example, White or mixed race congregations with active gay constituencies and an African-American congregation with a strong lay HIV champion were among the high HIV involvement case scenarios, compared to African-American congregations with a health emphasis but no lay HIV champion among the medium HIV involvement scenarios, and fundamentalist African-American and Latino congregations among the low HIV involvement scenarios. Two key factors that appeared influential across case scenarios included the existence of lay champions for HIV activities and the general theological orientation of the congregation. Highlights: Religious congregations can reach populations disproportionately affected by HIV. Case studies of 14 diverse urban congregations explored factors shaping HIV activity. QCA methods identified case scenarios of unique combinations of congregation factors. Two factors were influential across cases—lay champions and theological orientations. Dynamics are applicable to congregational involvement in other health issues.